THE EFFECT OF ATTITUDE HOMOPHILY AND PHYSICAL ATTRACTIVENESS ON PURCHASE INTENTION MEDIATED BY TRUSTWORTHINESS (A STUDY ON YOUTUBE INFUENCER TASYA FARASYA) - Fiania Gasebala; Putri Dwi Cahyani; Nonik Kusuma Ningrum (RADJA PUBLIKA, 2025)
This study aims to analyze whether the attitude homophily and physical attractiveness influencers affect the purchase intention of beauty products on YouTube, which is mediated by trustworthiness on beauty influencer Tasya Farasya. This research uses quantitative methods with the sampling technique in this study is non-probability sampling with purposive sampling method. The population in this study were active users of YouTube social media to view content on beauty products, while the research sample was people who had watched Tasya Farasya videos on YouTube with as many as 140 respondents. The results of this study indicate that attitude homophily has a positive and significant effect on trustworthiness, physical attractiveness has a positive and significant effect on trustworthiness, attitude homophily has no effect on purchase intention, physical attractiveness has a positive and significant effect on purchase intention, and trustworthiness has a positive and significant effect on purchase intention.